SATISFACTION OF CARERS OF PEOPLE WITH ADVANCED DEMENTIA: THEIR EXPERIENCES AT THE OF END OF LIFE. Issue 1 (1st March 2014) - Vickerstaff, V; Sampson, EL; Scott, S; Davis, S; Lord, K; Harrington, J; Elliott, M; Kupeli, N; Jones, L
Abstract : Introduction: Carers of people with advanced dementia (AdvD) have high burden and poor mental and physical health. The CoMPASs:IOn programme has developed and is piloting a complex intervention to improve end-of-life care for people with AdvD including support for families. Aim(s) and method(s): Pilot longitudinal cohort study of carers (target N=40) of people with AdvD (Functional Assessment Staging Scale 7a and above), assessed at study entry then monthly for 9 months or until patient death using the HADS, SF-12 and Satisfaction with Care at the End of Life in Dementia Scale (SWCEOLD). Results: 25 carers currently recruited (mean age 62, range 43–91; 68% female; 76% child of the person with dementia, 48% in paid employment). 92% of those they care for reside in care homes. Initial SWC-EOLD scores were 29.7 (range 13–40), consistent even in 7 carers whose relative died (mean score 30.3 (range 13–40) a month before death, 32.1 (range 13–40) after bereavement). On HADS (cut off ≥8), at initial assessment 40% had anxiety, 28% depression. Anxiety decreased over time; 20% have recorded anxiety 9 months later (7 carers). Two months post-bereavement, 14% of carers had anxiety or depression. At first assessment, SF-12 physical scores were 50 (range 33–58) remaining constant, mental health 48 (range 19–64) declining to 44 post death. Conclusion(s): It is feasible to recruit carers of people with AdvD and retain them into bereavement. Carers were satisfied with on-going care and around the time of death for the person with AdvD. Accrual continues for a further 4 months.